Water management strategies for polymer electrolyte fuel cells (PEFCs) employing microchannel flowfields - Daniels, Simone Monique (Department of Chemical Engineering, 2016)
Polymer electrolyte fuel cells (PEFCs) represent a promising energy conversion technology for automotive and portable applications. In order to achieve the high power densities required for these applications, the fuel cell needs to be operated in the high current density region where the rate of water production is at a maximum. This typically leads to the build-up of liquid water in the porous media and flowfield compartments of the fuel cell. The build-up of liquid water inhibits reactant gas transport to the catalyst layer, leading to a phenomenon called flooding. Flooding causes a rapid drop in cell voltage and is detrimental to fuel cell performance and durability. Microchannel flowfield designs possess characteristics which could potentially improve water removal from the fuel cell and also reduce the fuel cell system complexity. There is limited knowledge on the use of microchannels flow field designs in PEFCs, specifically how different operating conditions and different membrane electrode assembly (MEA) designs affect the overall performance and water management of a fuel cell using microchannel flow fields. This study investigated two water management strategies for PEFCs employing microchannel flowfields, namely manipulation of operating conditions and modification to the design of components within the MEA. Four different gas diffusion layer (GDL) cases were tested in a single cell environment at four different cathode flowrates and stoichiometric ratios. The cases consisted of a carbon GDL and three variants of a uniform structured metal GDL. The three metal GDL designs varied in terms of the wettability of the microporous layer coated on the surface of the metal GDL. Several in-situ diagnostic tests, namely polarisation curves, electrochemical impedance spectroscopy (EIS), pressure drop and voltage stability tests were conducted to determine the overall fuel cell performance and water management characteristics of the different GDL cases.